2022
DOI: 10.1111/ijfs.15607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐pressure‐modified soy 11S globulin on the gel properties and water‐holding capacity of pork batter

Abstract: The effects of high-pressure-modified soy 11S globulin (0.1, 200, and 400 MPa) on the gel properties, water-holding capacity, and water mobility of pork batter were investigated. The high-pressure-modified soy 11S globulin significantly increased (P < 0.05) the emulsion stability, cooking yield, hardness, springiness, chewiness, resilience, cohesiveness, the a * and b * values, and the G 0 and G 00 values of pork batter at 80 °C, compared with those of 0.1 MPa-modified globulin. In contrast, the centrifugal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Soy 11S globulin is a hexamer protein comprising a basic subunit and acid subunit linked by disulfide bonds, 7 which determines its high thermal stability, limiting its application in the production of low-temperature gel foods. 8 Additionally, it has been shown that soy 11S globulin has low emulsifying activity. 9 Numerous studies have been devoted to developing the functional properties of soy 11S globulin by physical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Soy 11S globulin is a hexamer protein comprising a basic subunit and acid subunit linked by disulfide bonds, 7 which determines its high thermal stability, limiting its application in the production of low-temperature gel foods. 8 Additionally, it has been shown that soy 11S globulin has low emulsifying activity. 9 Numerous studies have been devoted to developing the functional properties of soy 11S globulin by physical methods.…”
Section: Introductionmentioning
confidence: 99%
“…It has very good water retention, as well as gel and emulsification properties (Zhang et al, 2021). However, because it is a hexameric nonglycoprotein, the disulfide bonds increase the stability of the structure, and the initial denaturation temperature of soy 11S globulin is over 85°C (Kang, Chen, & Ma, 2016; Tang, 2019), limiting its use in food processing (Gao et al, 2020; Kang et al, 2022; Xie, Zou, Li, Kang, & Ma, 2022). Thus, it is necessary to improve the processing properties of soy 11S globulin by modification.…”
Section: Introductionmentioning
confidence: 99%